Development and validation of a recombinant Rap1-based lateral flow immunoassay for rapid serodiagnosis of bovine babesiosis in Kazakhstan - Kanatbek Mukantayev; Zhansaya Adish; Darkhan Kanayev; Laura Tokhtarova; Bisultan Abirbekov; Yergali Abduraimov; Aralbek Rsaliyev; Kanat Tursunov (Veterinary World, 2025)
Background and Aim: Bovine babesiosis, caused by Babesia bovis, poses significant economic challenges to Kazakhstan’s cattle industry. Early and accurate detection is crucial for interrupting transmission cycles, particularly in regions lacking advanced diagnostic infrastructure. This study aimed to develop a rapid lateral flow immunoassay (LFIA) using a recombinant C-terminal fragment of the recombinant rhoptry-associated protein 1 (rRap1) antigen for the serodiagnosis of bovine babesiosis.